Sarcolemmal-restricted localization of functional ClC-1 channels in mouse skeletal muscle - Lueck, John D. (The Rockefeller University Press, 2010)
Skeletal muscle fibers exhibit a high resting chloride conductance primarily determined by ClC-1 chloride channels that stabilize the resting membrane potential during repetitive stimulation. Although the importance of ClC-1 channel activity in maintaining normal muscle excitability is well appreciated, the subcellular location of this conductance remains highly controversial. Using a three-pronged multidisciplinary approach, we determined the location of functional ClC-1 channels in adult mouse skeletal muscle. First, formamide-induced detubulation of single flexor digitorum brevis (FDB) muscle fibers from 15–16-day-old mice did not significantly alter macroscopic ClC-1 current magnitude (at −140 mV; −39.0 ± 4.5 and −42.3 ± 5.0 nA, respectively), deactivation kinetics, or voltage dependence of channel activation (V(1/2) was −61.0 ± 1.7 and −64.5 ± 2.8 mV; k was 20.5 ± 0.8 and 22.8 ± 1.2 mV, respectively), despite a 33% reduction in cell capacitance (from 465 ± 36 to 312 ± 23 pF). In paired whole cell voltage clamp experiments, where ClC-1 activity was measured before and after detubulation in the same fiber, no reduction in ClC-1 activity was observed, despite an ∼40 and 60% reduction in membrane capacitance in FDB fibers from 15–16-day-old and adult mice, respectively. Second, using immunofluorescence and confocal microscopy, native ClC-1 channels in adult mouse FDB fibers were localized within the sarcolemma, 90° out of phase with double rows of dihydropyridine receptor immunostaining of the T-tubule system. Third, adenoviral-mediated expression of green fluorescent protein–tagged ClC-1 channels in adult skeletal muscle of a mouse model of myotonic dystrophy type 1 resulted in a significant reduction in myotonia and localization of channels to the sarcolemma. Collectively, these results demonstrate that the majority of functional ClC-1 channels localize to the sarcolemma and provide essential insight into the basis of myofiber excitability in normal and diseased skeletal muscle.